Combined C4d and CD3 immunostaining predicts immunoglobulin (Ig)A nephropathy progression. (February 2015) - Faria, B.; Henriques, C.; Matos, A. C.; Daha, M. R.; Pestana, M.; Seelen, M.
Summary A number of molecules have been shown recently to be involved in the pathogenesis and progression of immunoglobulin (Ig)A nephropathy (IgAN). Among these, we have selected C4d (complement lectin pathway involvement), CD3 (T cell marker, traducing interstitial inflammation), transglutaminase 2 (TGase‐2, involved in tissue fibrosis development) and p‐extracelluar‐regulated kinase (ERK)1/2 (protein kinase intracellular signaling molecule) to perform a panel of immunohistological biomarkers and assess its predictive value for disease progression. Immunohistochemical staining of these biomarkers was performed in paraffin sections from 74 renal biopsy cases with the clinical diagnosis of IgAN. Association between score analysis of these parameters and disease course was assessed through univariate and multivariate analysis, including baseline clinical and histological data. Univariate analysis showed that glomerular C4d, tubulointerstitial TGase2 and CD3 scores were associated with baseline proteinuria and disease progression. Multivariate analysis showed that only baseline estimated glomerular filtration rate (eGFR), C4d and CD3 were associated independently with progressive kidney disease (decline of at least 50% in the eGFR or progression to end‐stage renal disease (ESRD) during the follow‐up period). Establishing an accurate prediction model for IgAN progression is still a matter of research in clinical nephrology. The complement system, particularly lectin pathway activation, and T cell activation, have been shown previously to be potential modifiers of the disease course. Here we show that the combination of two histological biomarkers (C4d and CD3) can be a powerful predictor of IgAN progression and a potential useful tool for the clinical approach of this disease.